Aggravation of an injured dentato-rubro-thalamic tract in a patient with mild traumatic brain injury: A case report. Issue 43 (October 2017) - Jang, Sung Ho; Kwon, Hyeok Gyu
Abstract: Rationale: We report on a patient with mild traumatic brain injury (TBI) by follow-up diffusion tensor tractography (DTT), and observed for approximately nine monthsby serial diffusion tensor tractography (DTT). Patient concerns: A 66-year-old male patient was injured in a car crash. Approximately four weeks after the crash, he developed a tremor in the right hand and leg. His symptoms worsened over time. Diagnoses: Approximately six months after the crash, he developed a mild tremor in the left hand. Nine months after the crash, he manifested severe tremor in his right hand, mild resting and intentional tremor in his left hand and both legs, and mild trunkal ataxia. Interventions: N/A. Outcomes: On 3-week DTT, well reconstructed DRTTs were observed in both hemispheres, except for the thinned lower portion of the right DRTT. On 9-month DTT, the right lower DRTT had thinned compared with the 3-week DTT and showed a disruption at the upper portion. The left DRTT showed thinning in the lower portion and tearing in the upper portion compared with 3-week DTT. Lessons: Aggravation of an injured DRTT was demonstrated in a patient with mild TBI, using serial DTT examination.